DIFFICULTIES ENCOUNTERED BY THE BUGINESE LEARNERS IN PRODUCING ENGLISH SOUNDS - Sitti Nurpahmi (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2013)
Abstract: This paper discusses about difficulties encountered by Bugis learner in producing English phonemes. The learners who learn second language use their mother tongue to analyze the second language. They analyze the second language to find the differences and similarities both languages. The similarities can create ease to transfer the language, on the contrary the differences can creates difficulties. Based on the description above it informs that Bugis learners have difficulties in producing the following phonemes: The Labial consonant /f/ and /v/, The interdental consonant /θ/ and /d/, The alveolar consonant /z/, The consonant palatals /ŝ/ and /ž/, The vowel /æ/, The diphtong / iə, uə, əu, eə/, English also permits much longer sequences of consonant initially, medially, and finally in utterances. Both English and Buginese have consonant which are conveniently symbolized /t,d,s,z/. In English, however, these represent alveolar, whereas in Buginese they represent dentals. All of these differences constitute a major source of difficulty for the Bugis speakersin leaning English.Abstrak: Tulisan ini membahas tentang kesulitan yang dihadapi oleh pebelajar yang bahasa ibunya adalah bahasa Bugis dalam mengucapkan fonem. Pebelajar yang belajar bahasa kedua menggunakan bahasa ibu mereka untuk menganalisa bahasa kedua. Mereka menganalisa bahasa kedua untuk menemukan perbedaan dan persamaan diantara kedua bahasa. Persamaan akan memudahkan untuk mentansfer bahasa kedua, dan sebaliknya perbedaan dapat menyulitkan. Pebelajar yang bahasa ibunya adalah bahasa Bugis mempunyai kesulitan dalam menybutkan fnem-fonem berikut: konsonan bilabial/f/ dan /v/. konsonanm interdental /θ/ and /d/, konsonan alveolar/ z// the konsonan palatal /ŝ/ and /ž/, vokal /æ/, diftong / iə, uə, əu, eə/. Bahasa Inggris dan bahasa Bugis mempunyai konsonan /t,d,s,z/. Namun demikian dalam bahasa Inggris dikategorikan sebagai alveolar sementara dalam bahasa Bugis dikategorikan sebagai dental. Perbedaan-perbedaan tersebut menyebabkan kesulitan bagi pebelajar bahasa inggris untuk menghasilkan bunyi-bunyi dalam bahasa Inggris.